Mapping ActEarly: Using a child health map to evaluate a City Collaboratory programme on early promotion of good health and wellbeing - Patience Gansallo; Maria Bryant; Liina Mansukoski; Louise Padgett; Jessica Sheringham; Shahid Islam; Philip Garnett (PLoS ONE, 2026)
Background Public health is increasingly being viewed as the result of numerous interrelated elements within intricate systems. A systems mapping approach highlights the potential direct and indirect impacts of public health programmes, the contexts within which they take place and the relations between the multiple factors at play. We report on an approach to evaluate the extent to which a city-wide programme of interventions, delivered in two locations to improve child health (ActEarly) provided activities across the child health system and addressed early-life core outcomes which were selected based on priorities identified by key stakeholders. Methods Data from an ‘ActEarly project log’ and other information sources were used to gather a detailed picture of 68 projects that were delivered within the programme. We then used a matrix approach to map these activities against activities and outcomes from an existing child health map (CHM) of the determinants of child health inequalities and a project specific public health core outcome set (COS), developed by community and policy maker input, for systems-wide promotion of early life health and wellbeing. This was conducted alongside the creation of a new systems map and a network analysis to highlight how ActEarly operated across the children’s health system (scaled in proportion to the number of projects). Results and conclusions The map showed substantial ActEarly activity across all six CHM domains (95/139 factors) with most projects targeting the service and governance domains. There was a focus on service/governance areas of the child health system, rather than individual behaviour change, which aligned with ActEarly’s objective of influencing structural barriers to health. Projects also mapped well onto 32 of the 35 outcomes across the COS domains, with the exception of Adult Obesity, Safety at Home, and Domestic Abuse. This suggests that ActEarly aligned well with the priority outcomes from local representatives, partners and community groups.